Population structure of Neisseria gonorrhoeae based on whole genome data and its relationship with antibiotic resistance - Ezewudo,Matthew N.; Joseph,Sandeep J.; Castillo-Ramirez,Santiago; Dean,Deborah; del Rio,Carlos; Didelot,Xavier; Dillon,Jo-Anne; Selden,Richard F.; Shafer,William M.; Turingan,Rosemary S.; Unemo,Magnus; Read,Timothy D. (PeerJ, 2015)
Neisseria gonorrhoeae is the causative agent of gonorrhea, a sexually transmitted infection (STI) of major importance. As a result of antibiotic resistance, there are now limited options for treating patients. We collected draft genome sequence data and associated metadata data on 76 N. gonorrhoeae strains from around the globe and searched for known determinants of antibiotics resistance within the strains. The population structure and evolutionary forces within the pathogen population were analyzed. Our results indicated a cosmopolitan gonoccocal population mainly made up of five subgroups. The estimated ratio of recombination to mutation (r/m = 2.2) from our data set indicates an appreciable level of recombination occurring in the population. Strains with resistance phenotypes to more recent antibiotics (azithromycin and cefixime) were mostly found in two of the five population subgroups.
Keywords: Antimicrobial resistance; Population structure; Recombination; Whole genome sequence analysis; Genetic admixture